Harmony of Tradition and Sustainability: A Systematic Review of Management Strategies for Penglipuran Tourism Village - Nyoman Teja Adiastra; Putu Indah Rahmawati; I Made Agus Jana Januraga (Universitas Pendidikan Ganesha, 2026)
This study seeks to identify strategic themes, assess the incorporation of local values, and create a knowledge map derived from scientific literature pertaining to the administration of Penglipuran Tourism Village. This study employed a qualitative systematic review technique to assess 15 selected scientific articles published from 2015 to 2025. The study identified three primary findings: firstly, the literature reveals five strategic themes in the management of Penglipuran Tourism Village, which include the preservation of local wisdom, collaborative governance, environmental conservation, community participation, and marketing strategies grounded in legal certification. Secondly, native values such as awig-awig and Tri Hita Karana have been harmoniously incorporated into the village's regulations, social life, and economics, despite ongoing structural obstacles. The knowledge map offered an adjustable and scalable strategic framework that prioritizes cultural digitalization, community empowerment, and cross-sector collaboration for the creation of sustainable tourism villages. The research underscores the significance of multi- stakeholder engagement, digital innovation, and localized HR training as essential components for sustainability. The results are anticipated to provide a practical reference for policymakers, scholars, and managers of tourist villages in the development of culture-based and sustainable tourism models.